UJI RELIABILITAS DAN VALIDITAS MODIFIKASI NEUROPATHIC PAIN DIAGNOSTIC QUESTIONNAIRE DN4 TERHADAP LEEDS ASSESMENT NEUROPHATIC SYMPTOMS AND SIGN LANSS PADA PASIEN HIVAIDS - Luh Kadek Trisna Lestari, Putu Eka Widyadharma, Ketut Tuti Parwati Merati (NEURONA, 2013)
INTRODUCTION NEUROPATHIC PAIN DIAGNOSTIC QUESTIONNAIRE DN4IS A SCREENING TOOL FOR NEUROPATHIC PAIN CONSISTING OF 4 INTERVIEW QUESTIONS DN4 QUESTION AND PHYSICAL TEST IT HAS BEEN USED IN MANY LANGUAGES TO ASSESS NEUROPATHIC PAIN WITH GOOD RESULTS BUT THE TRANSLATION IN INDONESIAN LANGUAGE HAS NOT BEEN DONE BEFORE